2013
DOI: 10.1002/star.201200245
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of starch/EVA composite foams with surface modified kaolin

Abstract: Starch/EVA (ethylene-vinyl acetate copolymer)/modified kaolin nanocomposite foaming materials were prepared. The modified kaolin was obtained by g-methylacryloyl oxypropyl trimethoxysilane (silane coupling agent KH-570) as the nucleating agent. The effects of the modified kaolin were analyzed by activation index, and the structure was characterized by Fourier transform infrared (FT-IR) and SEM. The effects of modified kaolin on the mechanical properties and the cellular structure of the composite foams were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This was caused by the increased viscosity of the systems that prevented their expansion. Similar effects were produced by addition of modified kaolin and calcium carbonate, as reported by Zheng et al and Glenn et al , respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This was caused by the increased viscosity of the systems that prevented their expansion. Similar effects were produced by addition of modified kaolin and calcium carbonate, as reported by Zheng et al and Glenn et al , respectively.…”
Section: Resultssupporting
confidence: 83%
“…However, starch foams have some drawbacks such as poor mechanical properties, fragility, and ability to adsorb water . Various fillers have been used to improve the properties of starch foams such as addition of fibers , clay , proteins , wax , ethylene‐vinyl acetate copolymer (EVA) , and calcium carbonate . However, the hydrophilic characteristics of the starch foam can cause incompatibility with some hydrophobic fillers and they are also prone to aggregate during the foam production process.…”
Section: Introductionmentioning
confidence: 99%
“…6 Ji et al studied the addition of Inorganic powders such as ZnO to Eva foams as filler and found that inorganic additives strongly influenced the nucleation during foam formation, considerable changes in pores structure and mechanical properties. 7 Graphite, 8 kaolin, 9 starch, 10 lignin, 11 and other materials are also used as additives in powder form to improve properties of EVA foams.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge to produce PP/Kaol composites with desirable properties is the low compatibility between the interfaces polymer‐clay . The use of silanes couplings agents can be employed to improve this compatibility . The effects of the silane on the interfacial properties are determined by its molecular structure that interacts with the polymer matrix by means of hydrogen bonds or van der Waals forces .…”
Section: Introductionmentioning
confidence: 99%